Vital Dyes in Ophthalmology: a Chemical Perspective. (July 2014) - Badaro, Emmerson; Novais, Eduardo Amorim; Penha, Fernando Marcondes; Maia, Mauricio; Farah, Michel Eid; Rodrigues, Eduardo Buchele
Abstract Vital dyes have advanced diagnosis and surgical technique in various specialties, including oncology, gastroenterology and ophthalmology. Intra-operative and diagnostic dyes are finding uses in all areas of ophthalmology, including cornea, cataract, retina, glaucoma, orbit and conjunctiva. We provide a summary of current knowledge of the chemical concepts of vital dyes in ophthalmology. We review the properties of dyes, techniques of application, indications and complications in ocular surgery. Vital dyes represent an expanding area of research, and novel dyes deserve further investigation.